Analisis Perilaku Konselor Laktasi dalam Menunjang Keberhasilan ASI Eksklusif di Rumah Sakit Bina Kasih Pekanbaru - Sri Rentina; Siti Sindi Lailam Barokah; Sri Rahayu; Sri Wahyuni; Sufiarni Saputri (Universitas Malahayati Lampung, 2023)
ABSTRACT Exclusive breast milk (ASI) is breast milk given to babies from the time they are born until they are 6 months old without any additional or substitute food (except drugs, vitamins and minerals). The purpose of this study in general is to find out in-depth information on the behavior of lactation counselors in supporting the success of exclusive breastfeeding for mothers who give birth at Bina Kasih Hospital Pekanbaru. With variables of knowledge, attitudes, motivation, media information and education and the role of health workers. The type of research used was descriptive qualitative, with a total of 6 informants, consisting of lactation counselors, hospital supervisors and patients who gave birth at the hospital. From the results of the study it can be concluded that the counselor's concurrent duties as an inpatient officer makes the education delivered less effective, so that the practice of exclusive breastfeeding is less than optimal for mothers who give birth at Bina Kasih Hospital Pekanbaru. Keywords: Lactation Counselors, Exclusive Breast Milk ABSTRAK Air Susu Ibu (ASI) ekslusif adalah ASI yang diberikan kepada bayi sejak pertama dilahirkan samapi umur 6 bulan tanpa adanya makanan tambahan atau pengganti (kecuali obat, vitamin, dan mineral). Tujuan penelitian ini secara umum untuk mengetahui informasi yang mendalam terhadap perilaku konselor laktasi dalam menunjang keberhasilan ASI Ekslusif terhadap ibu yang melahirkan di RS Bina Kasih Pekanbaru. Dengan variabel pengetahuan, sikap, motivasi, media informasi dan edukasi dan peran petugas kesehatan. Jenis penelitian yang digunakan berupa deskriptif kualitatif, dengan jumlah informan 6 orang, terdiri dari konselor laktasi, supervisior rumah sakit dan pasien yang melahirkan di Rumah Sakit. Dari hasil penelitian dapat disimpulkan bahwa merangkapnya tugas konselor sebagai petugas rawat inap menjadi kurang efektifnya edukasi yang disampaikan, sehingga kurang maksimalnya praktik pemberian ASI Ekslusif kepada ibu yang melahirkan di RS Bina Kasih Pekanbaru. Kata Kunci: Konselor Laktasi, ASI Ekslusif